Quality-by-Design-Based Development of a Voxelotor Self-Nanoemulsifying Drug-Delivery System with Improved Biopharmaceutical Attributes - Aristote B. Buya; Romano Terrasi; Jérémie K. Mbinze; Giulio G. Muccioli; Ana Beloqui; Patrick B. Memvanga; Véronique Préat (MDPI AG, 2021)
Low aqueous solubility and poor oral bioavailability are limiting factors in the oral delivery of voxelotor, an antisickling agent. To overcome these limitations, a voxelotor self-nanoemulsifying drug delivery system was developed. Various oils, surfactants, and cosurfactants were screened for their solubilization potential for the drug. The area of nanoemulsification was identified using a ternary phase diagram. An experimental mixture design and a desirability function were applied to select SNEDDSs that contain a maximum amount of lipids and a minimum amount of surfactant, and that possess optimal emulsification properties (i.e., droplet sizes, polydispersity index (PDI), emulsification time, and transmittance percentage). The optimized SNEDDS formulation was evaluated for the self-emulsifying time (32 s), droplet size (35 nm), and zeta potential (−8 mV). In vitro dissolution studies indicated a 3.1-fold improvement in drug solubility from the optimized SNEDDS over pure drug powder. After 60 min of in vitro lipolysis, 88% of the voxelotor loaded in the SNEDDS remained in the aqueous phase. Cytotoxicity evaluation, using Caco-2 cells, indicated the safety of the formulation at 0.9 mg/mL. The transport of the voxelotor SNEDDS across Caco-2 monolayers was significantly enhanced compared to that of the free drug. Compared to the drug suspension, the developed SNEDDS enhanced the oral bioavailability (1.7-fold) of voxelotor in rats. The results suggest that further development of SNEDDSs for the oral delivery of voxelotor is needed.